2020
DOI: 10.1159/000507109
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Decompression Retinopathy with Macular Edema after Deep Sclerectomy with Intrascleral Implantation

Abstract: We report a case of ocular decompression retinopathy (ODR) with macular edema, diagnosed by optical coherence tomography, after a deep sclerectomy (DS) with an intrascleral implant, resolved with medical therapy 6 months later. The medical literature reports that in 14% of patients suffering from ODR, a pars plana vitrectomy was required, and 15% of patients had a poor final visual acuity. An otherwise healthy 75-year-old man with high myopia and a primary open-angle glaucoma, with previous intraocular pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Non-invasive OCTA and invasive UWF-FA were performed to assess the vascular structure of the posterior pole of the eye (Figure 3). In most of the previous reports, OCT scans of ODR were not included; therefore, a decrease in BVCA has been attributed to macular blot hemorrhage [12]. Mukkamala et al found macular edema in 5% of the ODR cases [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Non-invasive OCTA and invasive UWF-FA were performed to assess the vascular structure of the posterior pole of the eye (Figure 3). In most of the previous reports, OCT scans of ODR were not included; therefore, a decrease in BVCA has been attributed to macular blot hemorrhage [12]. Mukkamala et al found macular edema in 5% of the ODR cases [3].…”
mentioning
confidence: 99%
“…In most of the previous reports, OCT scans of ODR were not included; therefore, a decrease in BVCA has been attributed to macular blot hemorrhage [ 12 ]. Mukkamala et al found macular edema in 5% of the ODR cases [ 3 ].…”
mentioning
confidence: 99%